Influence of installing a virtual synchronous generator control on Lombok Island power grid with high penetration of PV plants - Setiadi, Herlambang; Mithulananthan, Nadarajah; Nuris Syifa, Baity; Ricky Ananda, Yoshiko; Cahya Anugrah Haebibi, Riski; Afif, Yusrizal (Institute of Advanced Engineering and Science, 2025)
Indonesia is a country with several islands, and providing clean energy in islanded power systems connected to a single main grid would be economy challenging. On the other hand, absence of inertia, system strength, and damping value in islanded power systems due to inverter interfaced renewable energy (RE) resources can cause significant decline of power system stability. The primary concern with integrating large scale photovoltaic (PV) power plant in an islanded power system is maintaining frequency and voltage stability. This research investigates the application of virtual synchronous generator (VSG) in Lombok’s Islanded power system, considering high penetration of PV. A thorough time domain simulation is performed with a detailed modelling of power system in Lombok Island to study the dynamic voltage and frequency stability. The simulation results show that the VSG improves both frequency and voltage stability in transient and steady state stages, ensuring smoother operation and faster stabilization time. It is found that the frequency deviation can be curtail up to 0.5% and the steady state can be increased up to 0.1%.